Optimalisasi E-Recruitment dan Penempatan Terhadap Prestasi Kerja Karyawan Pada Divisi Sales Lapangan PT Bina San Prima Sukabumi - Sofia Maulida; Erry Sunarya; Faizal Mulia Z (Journal of Economic, Bussines and Accounting (COSTING), 2023)
PT. Bina San Prima Sukabumi was the site of the research since the business is still relying on locals' connections for recruiting staff and its usage of the e-recruitment system is not yet fully effective. The same is true for employee placement; a rolling method is used instead of a single category to determine where an employee should be located. This study aims to ascertain the effects of e-recruitment and job placement on employee performance at PT. Bina San Prima's Field Sales Division. In this study, a quantitative associative descriptive methodology was used. 80 employees of PT. Bina San Prima were given the sample using the saturated sampling approach, and multiple linear regression was used for analysis. According to the study's findings, PT Bina San Prima Sukabumi has been able to increase staff performance through optimizing e-recruitment. Employee performance in the field sales sector of PT Bina San Prima Sukabumi is positively impacted by placement. So it makes sense that the field sales division of PT Bina San Prima Sukabumi has a successful implementation of the optimization of e-recruitment and staff placement on work performance.